Sinergi Antara Tradisi dan Teknologi Informasi: Merawat Tradisi Lokal Melalui Ritual Digital Platform Tiktok - Harahap, Zakiatu Husnil Fuadah; Akil, Rafiuddin (DAS Institute, 2025)
Indonesian local traditions have encountered difficulties in the digital age, particularly in their preservation via social media. TikTok, a social media platform focused on short videos, has emerged as a novel venue for communities to display and promote their cultural heritage. This essay seeks to elucidate the utilization of TikTok as a tool for the preservation of local traditions and the consequences stemming from the digitization process via the TikTok platform. Employing a descriptive qualitative methodology and media analysis, data gathered from five TikTok accounts that feature local tradition content demonstrates the efficacy of this platform in promoting local traditions. This study revealed that local traditions showcased through several creative mediums, including narrative, text films, voice-overs, carousels, and live streaming, have garnered audience interest and enhanced their engagement in local cultural dialogues. Nonetheless, obstacles are inevitably faced with the digitization of traditions, including the risks of excessive aestheticization, cultural commodification, and distortion of meaning resulting from adaptation to digital formats. This essay aims to elucidate techniques for leveraging social media to preserve local traditions, ensuring their authenticity and values remain pertinent for future generations.